Global Interest Rates, Currency Returns, and the Real Value of the Dollar - Engel, Charles; West, Kenneth D (American Economic Review, 2010)
The real value of the US dollar has fluctuated widely during the global financial crisis and its aftermath. Beginning in early 2008 through early 2009, the dollar strengthened against most currencies but weakened considerably in the intervening months. We propose a decomposi tion of the forces driving the real exchange rate into a long run real interest rate component and a residual risk premium component. If real interest rates in the United States rise rela tive to its partners, the value of the dollar should strengthen. Likewise, if the level risk premium on foreign interest-bearing assets rises, the dol lar should also strengthen. We find that little of the recent movements in the dollar are directly attributable to the real interest component, sug gesting that most of the movements are due to the residual risk premium component. There is a large and diverse literature that affords a role to real interest differentials and to risk premiums in determining the real value of a currency. Our approach is almost purely definitional. The only assumptions we rely on are those of stationarity?of the real exchange rate and the US-foreign real interest differen tial. Specifically, let qt denote the log of the real exchange rate, defined as the foreign con sumer price level (converted into dollar terms